2004
DOI: 10.1086/380756
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Observations of Simulated Radio Galaxies. I. Radio and X‐Ray Analysis

Abstract: We present an extensive synthetic observational analysis of numerically simulated radio galaxies designed to explore the effectiveness of conventional observational analyses at recovering physical source properties. These are the first numerical simulations with sufficient physical detail to allow such a study. The present paper focuses on extraction of magnetic field properties from nonthermal intensity information. Synchrotron and inverse Compton intensities were effective in providing meaningful information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…For example, Cheung et al (2007) demonstrated that observed proper motions of forward (superluminal) and reverse (subluminal) knots can be precisely reproduced by a 1D relativistic MHD simulation model. A very interesting work was presented in a series of papers by Jones et al (2001), Tregillis et al (2001aTregillis et al ( ,b, 2004, O'Neil et al (2006), and others where the authors have conducted extensive studies of high-resolution 2D and 3D MHD simulations of supersonic jets, exploring the influence of the jet Mach number and the ambient medium A88, page 2 of 12 on jet propagation and energy deposition over long distances. Obviously, only 3D simulations can reproduce the obliquity of the features in some jets observed with very high angular resolution, e.g.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…For example, Cheung et al (2007) demonstrated that observed proper motions of forward (superluminal) and reverse (subluminal) knots can be precisely reproduced by a 1D relativistic MHD simulation model. A very interesting work was presented in a series of papers by Jones et al (2001), Tregillis et al (2001aTregillis et al ( ,b, 2004, O'Neil et al (2006), and others where the authors have conducted extensive studies of high-resolution 2D and 3D MHD simulations of supersonic jets, exploring the influence of the jet Mach number and the ambient medium A88, page 2 of 12 on jet propagation and energy deposition over long distances. Obviously, only 3D simulations can reproduce the obliquity of the features in some jets observed with very high angular resolution, e.g.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…Additionally, we include a population of passive, nonthermal, relativistic cosmic ray particles in our models. These cosmic rays are transported, injected, accelerated, and aged in a self-consistent fashion to enable the construction of realistic synthetic observations (see, e.g., Jones et al 1999;Tregillis et al 2001aTregillis et al , 2004P. J. Mendygral 2010, in preparation) Here, we describe five simulations in which the initial ambient conditions are precisely the same, but the time histories of jet activity vary.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…We can refer to it as the astrophysical limit. This approach is more application oriented [17,31,30,28,29,36,18] and does not aim at studying f…”
Section: Introductionmentioning
confidence: 99%